Psychosocial Intervention Outcomes for Children with Congenital and Neonatal Conditions: Systematic Review. (26th April 2022) - Lamond, Bronwyn; Roberts, Samantha D; Miller, Steven P; Wade, Shari L; Williams, Tricia S
Abstract:  : There has been a historic lack of psychosocially geared treatment studies for congenital and neonatal conditions that impact brain development, despite well-established knowledge that these conditions impact cognitive development, quality of life (QoL), mental health, and academic success. Objective: The aim of the present study was to systematically investigate the research literature focusing on the effects of interventions in psychosocially geared programs for children with neonatal brain injury on school and psychological outcomes. Methods: Psychosocially geared programs broadly refer to interventions to improve parenting and school functioning, or child behavior, as well as other interventions that have a psychological component but may be more physically oriented, such as goal-directed physiotherapy. A comprehensive search of PubMed, Medline, PsychINFO, and Embase was completed between June and July 2020. The methodological quality of included articles was assessed using the Cochrane Risk of Bias Tool for Randomized Trials (RoB-2). Results and Conclusion: Twenty studies met the inclusion criteria and demonstrated adequate risk of bias (i.e., low risk of bias or some concerns). The studies included family ( n  =   2), parenting ( n  =   7), and child ( n  =   10) interventions. There is some evidence supporting the effectiveness of psychosocial interventions for children with neonatal brain injury and their families on academic outcomes, behavior, and QoL, indicated by positive intervention effects in 65% ( n  =   13) of studies.